2008
DOI: 10.1016/j.jcme.2008.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biofreeze and chiropractic adjustments on acute low back pain: a pilot study

Abstract: Objective: This randomized controlled study was designed to determine the pain-relieving effect of Biofreeze (Performance Health Inc., Export, PA) body surface application and chiropractic adjustments on subjects with acute low back pain (LBP). Methods: The data were collected at the baseline, 2 weeks after treatment, and 4 weeks after treatment for final analyses. Diversified manual adjustments were provided by licensed chiropractors twice a week for 4 weeks to both control and experimental groups. Biofreeze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Change in VAS pain scores with Biofreeze in various musculoskeletal conditions in relation to clinically important differences. Based on data from Bishop et al, 13 Zhang et al, 18 Topp et al, 21 and Sundstrup et al 23 Page and Alexander. J Perform Health Res.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Change in VAS pain scores with Biofreeze in various musculoskeletal conditions in relation to clinically important differences. Based on data from Bishop et al, 13 Zhang et al, 18 Topp et al, 21 and Sundstrup et al 23 Page and Alexander. J Perform Health Res.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized controlled trial by Zhang et al, 18 36 patients with acute back pain underwent chiropractic spinal manipulation twice a week for 4 weeks. The subjects were ) randomly assigned to either a control group (no additional treatment) or an experimental group in whom Biofreeze gel was applied to their back 3 times a day.…”
Section: Back Painmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduction in neck pain resulting from topically applied menthol is consistent with previous authors who reported that topical menthol reduces neck pain. from acute ankle sprains, 24 chronic lower back pain, 25 and delayed muscle soreness. 26 The pain-mitigating mechanism of the action of topical menthol application has been hypothesized by Wasner et al 27 The authors propose that as menthol stimulates TRPM8 receptors 28 in the skin, the activation threshold for vasoactive C nociceptors and cold-specific A delta fibers is lowered.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a randomized controlled study found that topical menthol combined with chiropractic adjustments reduced acute low back pain [26]. Thus, application of topical menthol is used to relieve pain of the musculoskeletal system and is widespread in sport medicine; however, double-blind randomized placebo-controlled trials are lacking and the acute effects of topical menthol application on chronic neuropathic pain remain unclear.…”
Section: Introductionmentioning
confidence: 99%